Organization of choir singing in churches as a means of raising and developing children - Vladimirovich Kolobanov, Alexey (2021)
The article deals with the study of historical aspects of children's choir singing in church tradition. The author considers characteristic features and origins of children's church choir singing. The reasons for using children's choir singing in Christian churches are investigated. The author characterizes the features of the conditions for utilization of children's choir singing in Christian churches. The distinction between children's church choir singing in the Orthodox East and Catholic West is shown. Children's choirs in Catholic churches were formed mainly from among orphan boys from orphanages at temples or monasteries. In the Catholic society of that time, childhood was not yet considered as a special status. Social assistance to children was included in the general program of care for unprotected segments of the population. However, they were destined for a compulsory religious education. In Orthodoxy, choir singing, along with the ability to read and write, was considered a necessary factor in the education of the ruling class and literate clergy. Thus, a more meaningful and profound educational program for future adults was introduced. In conclusion, the author states that children's choir singing, while being closely associated with church traditions and practice, introduces children to anagogic, educational and spiritual processes of the church ceremony.